Women's Sexuality and Relationship with Hysterectomy - Marni, Herti; Adnani, Syahredi Syaiful (Andalas Obstetrics And Gynecology Journal, 2020)
Sexuality is the most complex component, fundamental and main aspects of human behavior and life. Expressions of sexuality and intimacy are important throughout human life.Sexuality itself includes sex, gender identity and role, sexual orientation, eroticism, satisfaction, intimacy and reproduction. Sexuality is experienced and expressed through thoughts, fantasies, beliefs, attitudes, values, behavior, roles and relationships. Although sexuality includes the above dimensions, not everything can be experienced and expressed by everyone. This is influenced by biological, psychological, social, interactions economic, political, cultural, ethical, legal, religious and spiritual. Hysterectomy is a surgical removal of the uterus, which can be done by vaginal, abdominal, laparoscopic and robotic routes. The definition of "total hysterectomy" is a surgical procedure to remove the entire uterus with its cervix. In total hysterectomy is also accompanied by suturing in the cervix which will leave scar tissue. the uterine ligament is released, the uterosacral ligament cardinal that was previously attached to the cervix is sewn to the side of the vagina to hold the vagina in place. Three main changes after hysterectomy are anatomical changes, hormonal changes, and psycological changes. Hysterectomy effects women’s sexuality on various ways including sexual desire, sexual arousal, dan orgasmKeywords: sexuality, hysterectomy